Analisis Kesenjangan Ekonomi Daerah Perkotaan dan Pedesaan di Indonesia - Abdul Gafur; Salva Hunaya Rahmi; Fadlun Ahmadi (Economica Insight, 2025)
The economic gap between urban and rural areas in Indonesia is a persistent problem, despite various development programs. This study aims to analyze the factors causing this gap by 2025, covering aspects of income, infrastructure access, education, and economic opportunities. Data used are sourced from the Central Statistics Agency (BPS), the Ministry of Finance, and World Bank reports. The results show that income inequality remains quite high, with a lower Gini index in rural areas than in urban areas. However, disparities in access to public services, digital infrastructure, and non-agricultural employment opportunities remain significant. Integrated policies based on region and people are needed to narrow this gap.